Public Perception on the Adoption of ICT in the Contributory Pension Scheme - Monday, Nathaniel; Kalmai, Paul Musa (Kashere Journal of Politics and International Relations, 2024)
The study accessed the perception of academic and non-academic staff of Federal University of Kashere, Gombe State, Nigeria on the use of Information and Communication Technology in the contributory pension scheme. Nigeria has been reluctant in actively embracing and implementing the global trend of integrating Information and Communication Technology (ICT) into the public service. The prevailing culture of resisting change and adhering staunchly to the old and manual way of service delivery, which have shown limited effectiveness, has hindered our public sector from meeting global standard for service delivery. The main objective of the study is to measure public perception on the extent and effectiveness of information and communication technology usage in Nigeria contributory pension scheme and the role it has played in building public trust on the scheme. Survey research method was adopted, 300 copies of Four Likert Scale Questionnaire was distributed using multistage probability sampling across 6 Faculties of the University including the registry. Simple percentages and frequency tables was used to analze the data obtained. The finding revealed notably, a substantial portion of the respondents express a positive disposition towards the use of ICT in the scheme, suggesting a receptiveness to technology. Additionally, a majority have express dissatisfaction in the turnaround time and feedback mechanism. Due to the mixed landscape of perceptions and experiences, the research recommends for a balance and comprehensive approach in the implementation of ICT in the contributory scheme especially a regular feedback mechanism.